2021
DOI: 10.3892/mmr.2021.12535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of therapeutic hypothermia against renal injury in a rat model of asphyxial cardiac arrest: Α focus on the survival rate, pathophysiology and antioxidant enzymes

Abstract: Although multi-organ dysfunction is associated with the survival rate following cardiac arrest (CA), the majority of studies to date have focused on hearts and brains, and few studies have considered renal failure. The objective of the present study, therefore, was to examine the effects of therapeutic hypothermia on the survival rate, pathophysiology and antioxidant enzymes in rat kidneys following asphyxial CA. Rats were sacrificed one day following CA. The survival rate, which was estimated using Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In the present study, we found severe histological changes in kidney tissues. Jawad et al ( 26 ) and Kim et al ( 19 ) have reported the same pattern of histopathological changes in renal tissues after induction of asphyxial CA. Creatinine and BUN are the most frequently utilized endogenous indicators for assessing glomerular function ( 30 ).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In the present study, we found severe histological changes in kidney tissues. Jawad et al ( 26 ) and Kim et al ( 19 ) have reported the same pattern of histopathological changes in renal tissues after induction of asphyxial CA. Creatinine and BUN are the most frequently utilized endogenous indicators for assessing glomerular function ( 30 ).…”
Section: Discussionmentioning
confidence: 63%
“…A previous experiment has found that antioxidant enzymes including SOD-1, SOD-2, CAT, and GPx in kidneys exposed to ischemia for 30, 60, 90 min, 2 h, and 24 h are reduced significantly ( 40 ). Kim et al ( 19 ) have shown that immunoreactivity of antioxidant enzymes (SOD-1, SOD-2, CAT, GPx) in renal tissues are decreased at 1 day after I/R induction by asphyxial CA and that hypothermia treatment can increase the expression of antioxidants enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations